Evolutionary patterns of interleukin-6 (Il-6) and its impact on human health - Freitas, Arthur Felipe Ferreira de; Freitas, Nara Suzy Aguiar de; Mariano, Maria Helena Queiroz de Araújo; Rushansky , Eliézer; Maia, Maria de Mascena Diniz (Seven Editora, 2024)
Interleukin-6 (IL-6) is a multifunctional cytokine with properties pleiotropic derived from a polymorphic gene. The IL6 gene is located on the short arm of human chromosome 7 and containing four exons and four introns. The cytokine IL-6 is an important signaling agent between cells as the inflammatory reaction develops. Since cytokines are essential for life, studies show that the overproduction of IL-6 is often involved in various pathologies. It is well established that the frequency of different alleles of the cytokine genes varies between different populations of different species of mammals. Thus, this work aims to identify the relationship of synteny in relation to the preservation of order and the interaction between group of genes in the same chromosomal region based on the orthologs of the human IL6 gene in other five species of eutherian mammals and to investigate the selective signature of the IL6 gene in order to find conserved patterns in the genomes of mammals analyzed to observe their evolutionary history. We analyzed 40 genes adjacent to the IL6 gene in the genomes of Homo sapiens, Pan troglodytes, Gorilla gorilla, Pongo abelii, Camelus ferus and Equus asinus. The genetic sequences were obtained using the BLAST tool and aligned using the MEGA 11 program. We reviewed the literature looking for associations between the IL6 gene and its neighbors reported in previous studies. Finally, we analyzed the non-synonymous to synonymous substitution rates (dN/dS) between genomes in order to determine the selective signature of the IL6 gene. Among the 40 neighboring genes analyzed, only 11 were found to be in synteny, being present in all genomes. The conservation of these genes in different mammals suggests that IL6 and genes close to it may have evolved from a common ancestor and have been kept grouped together due to selective pressures during evolution. Furthermore, we found the NUP42 gene, which due to its moleculares properties, can influence the expression of the IL6 gene. The dN/dS ratio revealed a negative signature in the IL6 gene, which indicates that natural selection acts to maintain its conserved sequence, rejecting possible amino acid changes. Therefore, we conclude that our findings indicate that the IL6 gene remains conserved in the human genome during evolution. It is also noted that this gene may be influenced by its neighbors. With emphasis on the presence of the NUP42 gene, located close to IL6, which can act to regulate the expression of this cytokine in the body. Therefore, we suggest that future investigations include the evaluation of protein-DNA and protein-protein interactions in analyzes with the IL6 gene. DOI:https://doi.org/10.56238/sevened2024.007-030